2021
DOI: 10.1002/alz.12361
|View full text |Cite
|
Sign up to set email alerts
|

Modifying pathways by age and sex for the association between combined sleep disordered breathing and long sleep duration with neurocognitive decline in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL)

Abstract: Introduction:We aimed to determine whether obesity or metabolic syndrome (MetS) modify associations between sleep-disordered breathing (SDB), self-reported sleep duration (SD), and phenotypes of combined SDB/SD with 7-year neurocognitive decline (ND) in a community based-cohort of U.S. Hispanic/Latinos (N = 5500) in different age and sex groups. Methods:The exposures were baseline SDB (respiratory event index ≥ 15), sleepiness (Epworth Sleepiness Scale ≥ 10), SD (< 6 hours, 6-9 hours, ≥ 9 hours). The outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 43 publications
1
13
4
Order By: Relevance
“…The results of the present study are also in contrast to those of a recently published longitudinal study by our group in which only oldest-old participants (aged ≥75 years) with OSA demonstrated a greater longitudinal decline in processing speed over a 5 year period (Marchi et al, 2023). However, the different sample characteristics and methodological approaches make it difficult to compare the present study with those published earlier (Addison-Brown et al, 2014;Kaur et al, 2021;Marchi et al, 2023). In particular, the REGARDS and HCHS/SOL studies included middle-aged and older participants, whereas our study included a sample of older adults with a relatively narrow age distribution.…”
Section: Moderating Effect Of Age Sex Apoe4 and Obesitycontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of the present study are also in contrast to those of a recently published longitudinal study by our group in which only oldest-old participants (aged ≥75 years) with OSA demonstrated a greater longitudinal decline in processing speed over a 5 year period (Marchi et al, 2023). However, the different sample characteristics and methodological approaches make it difficult to compare the present study with those published earlier (Addison-Brown et al, 2014;Kaur et al, 2021;Marchi et al, 2023). In particular, the REGARDS and HCHS/SOL studies included middle-aged and older participants, whereas our study included a sample of older adults with a relatively narrow age distribution.…”
Section: Moderating Effect Of Age Sex Apoe4 and Obesitycontrasting
confidence: 99%
“…The absence of an age‐specific effect contrasts with the results of two previous population‐based studies which showed age modified the association between OSA and cognitive functioning, but in opposite ways. In the REGARDS study (Addison‐Brown et al, 2014) a weaker association between OSA and cognitive dysfunction was found with increasing age, whereas in the HCHS/SOL study (Kaur et al, 2021) a stronger association between OSA and cognitive decline was documented with increasing age particularly in participants of 65 years and older. The results of the present study are also in contrast to those of a recently published longitudinal study by our group in which only oldest‐old participants (aged ≥75 years) with OSA demonstrated a greater longitudinal decline in processing speed over a 5 year period (Marchi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep duration was treated as a categorical and continuous measure. The categorical cutoffs for sleep duration (<6 hours, 6–9 hours, >9 h) were chosen based on previous research on sleep duration and MRI measures, 29 and our own HCHS/SOL data using these categories of sleep 30 …”
Section: Methodsmentioning
confidence: 99%